Optimization of PCR Protocol for the Identification of Yeasts Isolated from Apis mellifera Honeycomb based on the ITS rDNA - Ayudya Fitri Arifa; Nirmala Fitria Firdhausi; Irul Hidayati; Yuanita Rachmawati; Moch. Irfan Hadi (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
Yeast is a microorganism that can be found in honeycomb. Yeast identification is a process to find and identify new species. One of which is molecular identification of yeast with rDNA sequences in the ITS region. Before carrying out molecular identification, it is necessary to optimize yeast DNA amplification methods to obtain good DNA sequences that ease the yeast identification process. The purpose of this study was to discover the optimum PCR (Polymerase Chain Reaction)protocols for the identification of yeasts isolated from Apis mellifera honeycomb based on the ITS rDNA. This study used 3 PCR (Polymerase Chain Reaction) protocols, i.e., from Kanti et al. (2018), Ediningsari (2008), and Maulana (2011). This results study shows that the optimum PCR protocol was from Maulana (2011), which produced clear and whole DNA fragment luminescences.